Use of Seitan and White Oyster Mushroom into Meatballs as Worth-Selling Tourism Food Product - Sonny Sanjaya; Ita Karnita; Tahani Imanda (Universitas Pendidikan Indonesia, 2023)
Seitan and white oyster mushrooms can be used in making meatballs, due to the lack of nutritional content in the choice of ordinary mushroom meatballs so the author makes a variant of mushroom meatballs with seitan which has many nutrients and higher nutritional value and can be an option for someone who wants to implement a healthy lifestyle and protein diet. The type of research used in this study is experimental research using organoleptic test of seitan and white oyster mushroom meatballs using seitan and oyster mushrooms. The number of samples is 10 to 20, and Consumer Panelist consisting of 30 to 100 people. The panelists who wrote themselves came from the neighborhood where they lived in the Bandung area, including students, lecturers, and various other professions. The production cost of making comparative meatballs is cheaper, at Rp. 850. The total cost of seitan and white oyster mushroom meatballs is Rp. 29,389, while comparative meatballs cost is Rp. 28,539. This difference occurs because some of the basic ingredients for making seitan and white oyster mushroom meatballs are more expensive, but the differences are not to significant, the results show that both meatballs have the same average value of 3.7. In addition, from several aspects both have their respective advantages and disadvantages, but the difference in value is not too far only 0.1-0.3 only, both can still be categorized as delicious, tasty, chewy and attractive. Therefore, from the above assessment, the experiment of Seitan and white oyster mushroom meatballs is declared suitable for marketing and sale.